UJI AKTIVITAS EKSTRAK ETANOL DAUN BELIMBING WULUH (Averrhoa bilimbbi L.) TERHADAP PENURUNAN KADAR GLUKOSA DARAH MENCIT PUTIH JANTAN YANG DIINDUKSI ALOKSAN - Aditya Maulana Perdana Putra; Desy Aulia; Amaliyah Wahyuni (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2017)
Diabetes mellitus is a metabolic disease characterized by the condition of hyperglycemia caused deficiency of insulin or insulin of resistance. From the incidence of diabetes mellitus that continues to increase then the treatment of diabetes mellitus need to be considered one of them using alternative medicine using averrhoa bilimbi L. One of the benefits averrhoa bilimbi L as antidiabetes. Part of the Averrhoa bilimbi L.. The aim of this study is to know the activity and effective dose of ethanol extract of Averrhoa blimbi L. leaf which can decrease blood glucose level in male mice induced alloxan. This study was conducted with pre and post test design with control group design on male white mice in May-June 2017. Twenty-five male white mice were divided into five groups: The leaves were extracted by using maceration method using 70% ethanol solvent. Blood glucose levels were measured before induction, after induction and after 14 days of treatment. The results showed that extract ethanol Averrhoa blimbi L. leaves can lower blood glucose levels after 14 days of treatment. The effective dose to decrease blood glucose levels is ethanol extract at a dose of 250 mg/kgBW because it has the same activity with positive control (metformin 100 mg/kgBW) in lowering blood glucose levels (ρ=1.000).